Cognición y lenguas andinas - Godenzzi, Juan Carlos (1999)
The Andean languages - Quechua and Aimara offers some keys to enter in the symbo/ic conceptual world of the Andes. Some semantic structures refered to the world and social praxis (pacha, yanantin, awqa, kuti, ayni, mink'a, mit'a) make transparents some schemes to organize the Andean world: complementarian coexistence, division, encounter of oposites and inversion; symetric, asysmetric and recursive reciprocity. At the same time, the context and day to day experiencies of people in the Andes are the basis of metaphorical ways to build the understanding of the universe.